1989
DOI: 10.1002/chin.198946072
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Grignard Reactions in the Solid State.

Abstract: The results from Grignard reactions of the halides (II) with benzophenone (I) are found to differ from those obtained in solution (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The grinding mode for solid-state reactions has been reported for some well-known reactions such as Grignard reactions (14), Reformatsky reactions (15), Aldol condensations (16), Dieckmann condensations (17), Knoevenagel condensations (18), Reductions (19), and others (20,21). Most of these reactions are carried out at room temperature in absence of solvent-free environment, using only a mortar and pestle.…”
Section: Nh 2 Nh 2 H 2 O + Introductionmentioning
confidence: 99%
“…The grinding mode for solid-state reactions has been reported for some well-known reactions such as Grignard reactions (14), Reformatsky reactions (15), Aldol condensations (16), Dieckmann condensations (17), Knoevenagel condensations (18), Reductions (19), and others (20,21). Most of these reactions are carried out at room temperature in absence of solvent-free environment, using only a mortar and pestle.…”
Section: Nh 2 Nh 2 H 2 O + Introductionmentioning
confidence: 99%
“…Solid-solid Grignard reactions with benzophenone and dried RMgX (R = Me, Et, Ph; X = I; Br) have been obtained in competition to reduction (to give diphenylmethanol) by cogrinding and aqueous workup (Scheme 15) [127]. Chiral six-coordinated crystalline Grignard reagents (which were obtained by enantiomeric crystallization) were used for asymmetric solid-solid Grignard syntheses.…”
Section: C-c Bond Formations With Carbonyl Compoundsmentioning
confidence: 99%
“…Reactions in dry media or under solvent free condition are especially appealing, as they provide an opportunity to work in an open vessel, thus avoiding the risk of high internal pressure development and with the possibility of up-scaling the reaction to the larger scale [3]. Recently, grindstone chemistry has been shown to be a highly viable green and rapid method for the synthesis of organic compounds without the complicacies associated with the use of different solvents, including water [4]. The proposed technique does not require external heating, leading to energy efficient synthesis and may be regarded as more economical and ecologically favorable procedure in chemistry [5].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed technique does not require external heating, leading to energy efficient synthesis and may be regarded as more economical and ecologically favorable procedure in chemistry [5]. Toda and coworkers showed that many of the exothermic organic reactions can be performed in good yield using mortar and pestle only [4]. Grindstone chemistry has been shown to be a very useful method for desktop as well as kilogram scale synthesis [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation